Numerical simulation of the gasification-reduction coupling process in the innovative multi-generation system. (5th March 2020) - Yang, Yiru; Li, Dongyue; Guo, Lei; Wang, Zhe; Guo, Zhancheng
Highlights: The ore feeding in the coal gasification was used as the partial oxidant and coolant. The overlap of the low-reductive and high-temperature distribution was disadvantage. The quality and yield of products (reduced iron and syngas) needs trade-offs. Solid particles become the largest heat expenditure item in the coupling process. Abstract: The combined coal gasification and flash ironmaking process (CG-FI) is considered as an innovative multi-generation system which can produce the qualified syngas and metallic iron simultaneously. In this work, a three-dimensional computational fluid dynamic (CFD) model was employed to investigate the critical gasification-reduction coupling process. The complete aggregation of the heterogeneous and homogeneous reactions, such as gasification reactions, water gas reactions, and reduction reactions, was associated with the calculation of the gas-particles flow problem. The turbulent structure, temperature/species distribution, and particle motion were investigated in this study. In addition, the effective-gas ratio, reduction degree, and heat utilization were predicted with variant ore/coal ratios to explore the optimum condition. It was shown that the influence of the ore feed on the velocity distribution is limited. However, the structure of the high-temperature zone was highly dependent on it and was transferred from a " ∧ "-shape distribution to a " ∨ "-shape when the ore feed was increased. The varied effective-gas ratio demonstrated a tendency of declining first and elevating later, in which the least value was determined to 70.80%. Our findings revealed two feasible operating conditions to attain high-quality products in the low-ore/coal-ratio cases or the qualified products of a larger amount in the high-ore/coal-ratio cases.